PENGETAHUAN BAHASA ARAB DALAM MEMAHAMI BIAS GENDER PADA TERJEMAHAN AL-QURAN VERSI KEMENTERIAN AGAMA - Wahyuni, Imelda (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2016)
Arabic language as a means of communication has an important role in human life. In particular, Arabic is the language of religion for Muslims. Al-Quran as a guide to moslims uses the Arabic language. Some translations of the Qur'an by Ministery of Religious of Indonesia are gender bias. This can be minimized by translating using specific approaches and methods, in order to have the translation and interpretation based on a gender perspective. So that women do not feel discredited, and subordinate to live a life together with men.